Astigmatism in Monkeys with Experimentally Induced Myopia or Hyperopia - KEE, CHEA-SU (2005)
PURPOSE: Astigmatism is the most common ametropia found in humans and is often associated with large spherical ametropias. However, little is known about the etiology of astigmatism or the reason(s) for the association between spherical and astigmatic refractive errors. This study examines the frequency and characteristics of astigmatism in infant monkeys that developed axial ametropias as a result of altered early visual experience. METHODS: Data were obtained from 112 rhesus monkeys that experienced a variety of lens-rearing regimens that were intended to alter the normal course of emmetropization. These visual manipulations included form deprivation (n = 13); optically imposed defocus (n = 48); and continuous ambient lighting with (n = 6) or without optically imposed defocus (n = 6). In addition, data from 19 control monkeys and 39 infants reared with an optically imposed astigmatism were used for comparison purposes. The lens-rearing period started at approximately 3 weeks of age and ended by 4 to 5 months of age. Refractive development for all monkeys was assessed periodically throughout the treatment and subsequent recovery periods by retinoscopy, keratometry, and A-scan ultrasonography. RESULTS: In contrast to control monkeys, the monkeys that had experimentally induced axial ametropias frequently developed significant amounts of astigmatism (mean refractive astigmatism = 0.37 ± 0.33 D [control] vs. 1.24 ± 0.81 D [treated]; two-sample t-test, p < 0.0001), especially when their eyes exhibited relative hyperopic shifts in refractive error. The astigmatism was corneal in origin (Pearson’s r; p < 0.001 for total astigmatism and the JO and J45 components), and the axes of the astigmatism were typically oblique and bilaterally mirror symmetric. Interestingly, the astigmatism was not permanent; the majority of the monkeys exhibited substantial reductions in the amount of astigmatism at or near the end of the lens-rearing procedures. CONCLUSIONS: In infant monkeys, visual conditions that alter axial growth can also alter corneal shape. Similarities between the astigmatic errors in our monkeys and some astigmatic errors in humans suggest that vision-dependent changes in eye growth may contribute to astigmatism in humans.